2018
DOI: 10.1186/s12883-018-1150-0
|View full text |Cite
|
Sign up to set email alerts
|

Marathons and myasthenia gravis: a case report

Abstract: BackgroundThe cardinal symptoms of auto-immune myasthenia gravis are fatigue and weakness. Endurance events such as marathon running would seem incompatible with this chronic disease. Many patients stop sport altogether. There is limited literature of patients with auto-immune myasthenia gravis undergoing regular endurance exercise.Case presentationWe report the case of a 36-year-old female who began long-distance running whilst experiencing initial symptoms of myasthenia gravis. She was diagnosed with auto-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This is in line with the minimum recommended for elderly healthy adults [33]. Single patients with generalized MG and AChR antibodies that have successfully completed both several marathons and ultramarathons have been reported [34,35], further supporting the safety of exercise in MG.…”
Section: The Listed Intervention Studies Applied Various Training Pro...supporting
confidence: 78%
“…This is in line with the minimum recommended for elderly healthy adults [33]. Single patients with generalized MG and AChR antibodies that have successfully completed both several marathons and ultramarathons have been reported [34,35], further supporting the safety of exercise in MG.…”
Section: The Listed Intervention Studies Applied Various Training Pro...supporting
confidence: 78%
“…There is a paucity of information on MG patients and sports participation and no clear guidelines for athletes with MG (7,63,64). To our knowledge, four case reports exist on athletes with MG and are summarized in Table 2.…”
Section: Mg and Sports Participationmentioning
confidence: 99%
“…Although few studies explicitly focused on safety and not all studies reported AEs, an important finding from this review, from precedent reviews and published case reports, 13,[38][39][40] is that there is no data to support exercise as a harmful intervention in MG. Only four studies explicitly stated that participants had stable disease. There is no study to date demonstrating evidence of an exercise-related myasthenic crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise could also counter possible corticotherapy-induced myopathy and osteoporosis from long-term corticosteroid use. Further, exercise could play an immunomodulatory role in MG. 13 In addition, unlike many pharmacological agents, exercise has minimal, if any, side effects when adapted to the individual.…”
Section: Introductionmentioning
confidence: 99%